The complete guide to shelter skills, tactics, and techniques - McCullough, Jay (US Army survival series, 2016)
Here in this critical guide is all the important safety techniques that you ll need to know in order to survive in just about any condition. From designing a makeshift earthquake shelter to constructing a water well, "The Complete Guide to Shelter Skills, Tactics, and Techniques" has got you covered. Within these pages, you ll find information on the best way to: Choose the best building materials. Select the best ambushing positions in any situation.